(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new genus and species, Kissrhizaecus hungaricus gen. et sp. nova, is described from the subfamily Rhizoecinae. A review, phylogeny and a key for genera are given for the subfamily. With this new description the number of genera in the subfamily Rhizoecinae increased to 16, and to 13 in the tribe Rhizoecini. The subfamily Rhizoecinae now contains 210, and. the tribe Rhizoecini 186 species. Two main lines known in the subfamily, the tribes of Rhizoecini and Xenococcini. In the tribe Rhizoecini based on morphological and zoo geographical data two phylogenetic lines presented. A new generic name Hambletonrhizaecus is proposed instead of Hambletonia Kozar & Foldi, 2004.